Contextual Integration through Computation: Algorithmic Approaches for Incorporating Lattice Patterns into Facade Designs - Bajracharya, Milind Raj; Uprety, Sanjaya (Journal of Engineering Technology and Planning, 2023)
Context and technology have significantly shaped architectural design throughout history, with contextuality playing a vital role in assigning meaning to designs. In light of computational tools and algorithms that revolutionize architectural design, enabling intricate and complex building geometries within shorter timeframes and heightened efficiency, this study aims to underscore the potential of algorithmic façade design. It focuses on contextual integration, utilizing the Newari lattice window as a foundational element for design exploration. The study employed computational modeling with parametric tools, scripting, and generative algorithms to create digital models that reflect the Newari lattice window pattern and fractal geometry. It utilized Text-Based Language (TBLs) like Python and Visual-Based Language (VBLs) like Grasshopper for visual experimentation and precision. Demonstrated through the re-design of the façade of the existing commercial building, Civil Mall, a significant building in Kathmandu Valley’s urban landscape, the research showcases algorithmic prowess in seamlessly integrating traditional Newari wisdom into intricate geometrical patterns. By transcending manual methods through recursion, iteration, randomness, and embracing unforeseen possibilities, the study establishes a foundational reference, enriching Nepal's architectural discourse beyond the traditional versus modern binary. This might be helpful in fostering a distinctive modern architectural language unique to Nepal. The study holds potential for further research on the prevailing traditional architectural forms and geometry in the country.